Biodiversity conservation research challenges in the 21st century: A review of publishing trends in 2000 and 2011. Issue 54 (December 2015) - Velasco, David; García-Llorente, Marina; Alonso, Blanca; Dolera, Agustín; Palomo, Ignacio; Iniesta-Arandia, Irene; Martín-López, Berta
Highlights: There has been an increasing collaboration between disciplines in 2011 relative to 2000. Europe, Oceania and North America are overrepresented in conservation science. Most studies focused on analyzing species threats, mostly of mammals and birds. Biodiversity conservation research should progress towards a 'people and nature' thinking. Abstract: The Strategic Plan for Biodiversity 2011–2020 recognizes the increasing importance of scientific knowledge to support conservation policies and decision making. In this study, we assessed the tendency of such knowledge in the first decade of the 21st century. We carried out a systematic review of publications in biodiversity conservation, considering the following aspects: type of research, main topic of study, object of study (i.e. biodiversity organizational level, taxonomic groups and ecosystems), pressures and drivers of change, as well as geographical distribution. In total, 966 publications were analyzed within the three journals with higher academic reach in the field under study: Biodiversity & Conservation, Biological Conservation, and Conservation Biology. Our results show that there are several biases in scientific knowledge associated with the object of study, and analyzed drivers of changes, as well as geographical distribution. However, research trends are not uniform along the first decade of 21st century, as there are some differences between 2000 and 2011 regarding the main topic of the study, the spatial scale and geographical region, and the analyzed ecosystems. We finally discuss the implications of current knowledge trends in biodiversity conservation for achieving the targets delineated by the Strategic Plan for Biodiversity 2011–2020.